Preoperative Lateralization Modalities for Cushing Disease: Is Dynamic Magnetic Resonance Imaging or Cavernous Sinus Sampling More Predictive of Intraoperative Findings? - Sun, Hai; Yedinak, Chris; Ozpinar, Alp; Anderson, Jim; Dogan, Aclan; Delashaw, Johnny; Fleseriu, Maria (Journal of Neurological Surgery Part B: Skull Base, 2015)
Objective To analyze whether cavernous sinus sampling (CSS) and dynamic magnetic resonance imaging (dMRI) are consistent with intraoperative findings in Cushing disease (CD) patients.Design Retrospective outcomes study.Setting Oregon Health & Science University; 2006 and 2013.Participants A total of 37 CD patients with preoperative dMRI and CSS to confirm central adrenocorticotropic hormone (ACTH) hypersecretion. Patients were 78% female; mean age was 41 years (at diagnosis), and all had a minimum of 6 months of follow-up.Main Outcome Measures Correlations among patient characteristics, dMRI measurements, CSS results, and intraoperative findings.Results All CSS indicated presence of CD. Eight of 37 patients had no identifiable tumor on dMRI. Three of 37 patients had no tumor at surgery. dMRI tumor size was inversely correlated with age (rs = − 0.4; p = 0.01) and directly correlated to intraoperative lateralization (rs = 0.3; p < 0.05). Preoperative dMRI was directly correlated to intraoperative lateralization (rs = 0.5; p < 0.002). CSS lateralization showed no correlation with intraoperative findings (rs = 0.145; p = 0.40) or lateralization observed on preoperative dMRI (rs = 0.17; p = 0.29). Postoperative remission rate was 68%.Conclusion dMRI localization was most consistent with intraoperative findings; CSS results were less reliable. Results suggest that small ACTH-secreting tumors continue to pose a challenge to reliable preoperative localization.
Keywords: cavernous sinus sampling; Cushing disease; magnetic resonance imaging; intraoperative lateralization